Incidence of Mucositis in Patients Treated With Temsirolimus-Based Regimens and Correlation to Treatment Response. (25th March 2014) - Liu, Xiaochun; LoRusso, Patricia; Mita, Monica; Piha-Paul, Sarina; Hong, David S.; Fu, Siqing; McQuinn, Lacey; Asatiani, Ekaterine; Doyle, Lawrence A.; Chen, Helen X.; Hess, Kenneth R.; Kurzrock, Razelle; et al.
Abstract : Mucositis may limit the therapeutic window for mammalian target of rapamycin inhibitor-based combination therapy, necessitating treatment interruptions and/or dose reductions. Optimizing treatment or prophylactic interventions for mucositis will enable patients to continue effective treatment while maintaining good quality of life.